275. Comparison of Cefazolin versus Nafcillin for Methicillin-Susceptible Staphylococcus aureus Bacteremia with a Deep-Seated Source. (31st December 2020) - Mersinger, Katherine E; Athans, Vasilios; Binkley, Amanda; Binkley, Shawn; Hamilton, Keith W; Redline, Gretchen; Saw, Stephen; Dutcher, Lauren
Abstract: Background: Historically, anti-staphylococcal penicillins have been the treatment of choice for methicillin-susceptible Staphylococcus aureus (MSSA) infections. However, cefazolin may have advantages over these agents including convenience and tolerability. Despite several studies finding similar rates of clinical efﬁcacy using cefazolin with fewer adverse drug events, some prescribers remain hesitant to use this agent due to concern for an inoculum effect in deep-seated infections. The purpose of this study was to compare cefazolin and nafcillin for the treatment of MSSA bacteremia with exclusively deep-seated sources. Methods: Adult patients who were admitted with MSSA bloodstream infections (BSI) treated with cefazolin or nafcillin between March 2017 and October 2019 were identified. Patients were included if their BSI had a deep-seated source, defined as endocarditis, osteomyelitis, septic arthritis, pneumonia, prosthetic material, mediastinitis, or abscess. Patients were excluded if they had polymicrobial BSI, central nervous system infection, or received less than 7 days of therapy. The primary efﬁcacy outcome (PEO) was a composite of treatment failure, 60-day mortality, and 60-day infection relapse, and was assessed using multivariate logistic regression. The primary safety outcome (PSO) was discontinuation of therapy due to adverse drug events, which was assessed with a chi-square test. Results: A total of 164 patients were included in this analysis (141 treated with cefazolin and 23 with nafcillin). There were no significant differences in the baseline characteristics collected (Table 1), and the most common deep-seated sources were prosthetic material and endocarditis. Treatment with nafcillin was not found to be protective against the PEO in multivariate analysis (aOR, 1.19; 95% CI, 0.42 to 3.39; P = 0.75), and the PSO was reached significantly more often among nafcillin recipients compared to those treated with cefazolin (7/23 [30.4%] versus 8/141 [5.7%], P < 0.0001). Conclusion: Though the sample size was smaller than desired, cefazolin and nafcillin appeared to have similar efficacy for the treatment of MSSA BSIs with deep-seated sources. Nafcillin was associated with significantly more adverse drug events leading to discontinuation of therapy. Disclosures: All Authors : No reported disclosures